2014
DOI: 10.3141/2407-03
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ultrasonic Tomography to Detect Structural Impairment in Tunnel Linings

Abstract: Tunnel inspection is a challenging problem because of high-volume traffic and routine operations in naturally aggressive environments. The need to keep tunnels open during inspection and minimize tunnel closures and user delays must be carefully balanced with the need to conduct in-depth lining inspections to ensure the safety of drivers. This paper describes the laboratory validation and field performance of a recently developed in-depth nondestructive testing technology for the detection of impairments in tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…Studies have shown that these methods can effectively detect defects in tunnel linings and achieve satisfactory detection results [6][7][8]. The combination of multiple techniques [9,10] can especially enhance the identification and localization of the defects. Among these methods, GPR, particularly vehicle-mounted GPR [11], is more efficient and widely used in high-speed railway tunnel inspections [12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that these methods can effectively detect defects in tunnel linings and achieve satisfactory detection results [6][7][8]. The combination of multiple techniques [9,10] can especially enhance the identification and localization of the defects. Among these methods, GPR, particularly vehicle-mounted GPR [11], is more efficient and widely used in high-speed railway tunnel inspections [12].…”
Section: Introductionmentioning
confidence: 99%
“…Stratified analysis evaluates the extent of the object's shedding and cracking. White et al [10] described the use of a low frequency ultrasonic detection system which successfully detected the presence of clay blocks on two of the three levels of interest in the pavement slab. The defects in the large-scale concrete structures or on the concrete surfaces were not involved in the previous reported works; and also, the internal details and shape of defects were not considered, which may introduce unexpected errors to the tomography images.…”
Section: Introductionmentioning
confidence: 99%
“…The main influencing features for TTBTs have been comprehensively studied [ 24 ]. Ultrasonic tomography (UST) is a nondestructive testing technology for the detection of impairments in tunnel lining [ 25 , 26 ]. For lining surface defect detection, an autonomous robot with computer vision system has been developed to inspect tunnel crack and efflorescence [ 27 ].…”
Section: Introductionmentioning
confidence: 99%